MANAJEMEN LABA, KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN : PERAN PERENCANAAN PAJAK SEBAGAI MODERASI: EARNING MANAGEMENT, DIVIDEND POLICY AND CORPORATE VALUE: THE ROLE OF TAX PLANNING AS MODERATION - Dumex Bahari Nasution; Zirman Zirman; Fajar Odiatma; Rheny Afriana Hanif (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This study analyzes earnings management and dividend policy's effect on business value, then tests tax planning as moderation. This study's population is raw material producing companies registered on the Indonesia Stock Exchange for 2018-2020, hence a purposive sample of 25 companies was used. Data processing with regression reveals earnings management affects firm value, dividend policy affects firm value, tax planning cannot moderate the effect of earnings management on firm value, but it can reduce the effect of dividend policy on firm value